Cold source of atomic hydrogen for loading large magnetic traps - Semakin, Aleksei; Ahokas, Janne; Hanski, Otto; Dvornichenko, Slava; Kiilerich, Tom; Nez, Francois; Yzombard, Pauline; Nesvizhevsky, Valery; Widmann, Eberhard; Crivelli, Paolo; Vasiliev, Sergey (Springer Science and Business Media LLC, 2025)
We present a design and performance tests of an intense source of cold hydrogen atoms for loading large magnetic traps. Our source is based on a cryogenic dissociator of molecular hydrogen at 0.6 K followed by a series of thermal accommodators at 0.5, 0.2 and 0.13 K with inner surfaces covered by a superfluid helium film. All components are thermally anchored to corresponding stages of a dilution refrigerator. The source provides a continuous flux of 7 x 10(13) H atoms/s in a temperature range of 130-200 mK. We have successfully used the source for loading a large Ioffe-Pritchard magnetic trap recently built in our laboratory (Ahokas et al. in Rev Sci Instrum 93(2):023201, 2022). Calorimetric measurements of the atomic recombination heat allow reliable determination of the atomic flux and H gas density in the trap. We have tested the performance of the source and loading of H atoms into the trap at various configurations of the trapping field, reducing the magnetic barrier height to 75% and 50% of the nominal value of 0.8 T (0.54 K) as well as at the open configuration of the trap at its lower end, when the atoms are in contact with the trapping cell walls covered by a superfluid helium film. In the latter case, raising the trapping cell temperature to 200-250 mK, the low-field seeking atoms at densities exceeding 10(11) cm(-3) can be stored for the time over 10(3) s, sufficiently long for experiments on precision spectroscopy of cold H gas.